THE EFFECT OF HIGH PERFORMANCE WORK SYSTEM ON JOB SATISFACTION, THROUGH THE ROLE OF BURNOUT MEDIATION AND MOTIVATION - Dheatasya Ezra Willenda; Desy Prastyani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Healthcare workers are the frontline of patient care, making it essential to implement work systems that support their well-being and motivation. High Performance Work System (HPWS) is considered a strategic approach to enhancing employee performance and job satisfaction. This study aims to examine the effect of HPWS on nurses’ job satisfaction, with burnout and work motivation as mediating variables. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected from 265 nurses working at private hospitals in Jakarta using purposive sampling techniques. The results revealed that HPWS has a significantly positive effect on job satisfaction and work motivation, and a significantly negative effect on burnout. Furthermore, burnout negatively affects job satisfaction, while work motivation has a positive effect. Mediation analysis showed that burnout and work motivation significantly mediate the relationship between HPWS and job satisfaction. This study contributes to the human resource management literature by emphasizing the importance of implementing HPWS practices in creating a healthy and productive work environment, which ultimately enhances employee well-being, particularly in the healthcare sector.